2013
DOI: 10.1007/s11033-013-2595-2
|View full text |Cite
|
Sign up to set email alerts
|

High glucose induces mitochondrial p53 phosphorylation by p38 MAPK in pancreatic RINm5F cells

Abstract: Pancreatic β-cell death in type 2 diabetes has been related to p53 subcellular localisation and phosphorylation. However, the mechanisms by which p53 is phosphorylated and its activation in response to oxidative stress remain poorly understood. Therefore, the aim of this study was to investigate mitochondrial p53 phosphorylation, its subcellular localisation and its relationship with apoptotic induction in RINm5F cells cultured under high glucose conditions. Our results show that p53 phosphorylation in the mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…Hyperglycemia promotes p53 phosphorylation which correlates with activation of pro-apoptotic proteins such as Bax. 29 Furthermore, Hinault et al (2011) demonstrated that in p53 knockout mice, the β-cell population regenerate and rescue the diabetic phenotype in this animal model. 30 According to above mention statements, it can be stated that up regulation of the apoptosis pathways are implicated in the development of type 2 diabetes.…”
Section: Discussionmentioning
confidence: 87%
“…Hyperglycemia promotes p53 phosphorylation which correlates with activation of pro-apoptotic proteins such as Bax. 29 Furthermore, Hinault et al (2011) demonstrated that in p53 knockout mice, the β-cell population regenerate and rescue the diabetic phenotype in this animal model. 30 According to above mention statements, it can be stated that up regulation of the apoptosis pathways are implicated in the development of type 2 diabetes.…”
Section: Discussionmentioning
confidence: 87%
“…Post-translational modifications of p53, including phosphorylation, are common ways to activate p53 in response to DNA damage and perturbation of phospholipid homeostasis [57]. The increased phosphorylation of p53 correlates with an increase in reactive oxygen species, a release of cytochrome c, and an increase in the rate of apoptosis [58]. Therefore, we hypothesize that the significant increase of Pp53/p53 ratio in Caco-2 cells incubated with high glucose is related to glyco-oxidative stress and contributes to apoptosis pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of MAPK pathways may lead to either cell survival or apoptosis depending on cellular contexts and stimuli [29]. It has been reported that high glucose induces p53-dependent mitochondrial apoptosis of pancreatic RINm5F cells via activation of p38 MAPK [30]. Inhibition of p38 MAPK has been shown to prevent pancreatic b cell apoptosis after islet transplantation in a canine model [31].…”
Section: Discussionmentioning
confidence: 99%